Group exercise for adults and elderly: Determinants of participation in group exercise and its associations with health outcome - Satoru Kanamori; Tomoko Takamiya; Shigeru Inoue (Japanese Society of Physical Fitness and Sports Medicine, 2015)
Physical activity may be carried out alone or in a group. No comprehensive studies have been conducted on the associations between group exercise and health outcomes, the mechanisms underlying the associations with health outcomes, and determinants of participation in group exercise. The aim of this article is to review the associations and mechanisms between group exercise and health outcomes, and the determinants of participation in group exercise among healthy adults and the elderly without specific illnesses. Group exercise may reduce the risk of physical and mental illness by improving adherence to physical activity, psychological factors, and social relationships. While there may potentially be various determinants of group exercise, previous research has only examined specific demographic and environmental factors. Among the studies discussed in this review, few studies examined the differences between individual exercise and group exercise. Thus, the unique effects and determinants of group exercise remain unclear. Further studies examining these points are needed to develop a more complete knowledge base on group exercise.